ANALYSIS OF THE FINANCIAL BEHAVIOR OF YOUNG UNIVERSITY STUDENTS REGARDING PERSONAL PLANNING AND INDEBTEDNESS - Cattani, Damaris Silva dos Santos (2023)
The study aimed to identify the financial behavior in relation to the indebtedness and the planning of the personal finances of the young students of a private university in Santa Maria / RS. The research sought to describe the financial reality of the students, identify the practices used to avoid indebtedness and understand the understanding and the importance of the theme for those investigated. For this purpose, a descriptive, quantitative and survey research was carried out, with the application of a questionnaire, divided into three sections, totaling 50 students from the administration, accounting and economic sciences courses. Most participants work in private, female, single companies, live with other people and spend less than they receive. The results showed that students have a conservative profile and use traditional techniques to control monthly expenses. In addition, they make decisions about their expenses based on professional and personal experiences, managing resources based on daily needs. As for the relevance of financial education, academics understand the importance of the theme, emphasize the inclusion of the subject in basic education and showed interest in opportunities so that they could learn more about financial planning. This research achieved its purpose of emphasizing the importance of financial planning to obtain adequate behavior in relation to consumption decisions.